Uso de biomassas não refinadas no desenvolvimento de espumas renováveis - Silva, Victória Barros Pinheiro da (Universidade Federal de São Carlos, 2025)
As plastic waste continues to accumulate on our planet, it is essential to explore sustainable alternatives that can match the performance of non-renewable polymeric materials. In order to replace lightweight materials such as plastic foams, the aim of this study is to use a sustainable and economical route to produce foams, with the application of plant biomass in the form of unrefined lignocellulosic particles of sugarcane bagasse (SB) and eucalyptus industrial waste (EIW), incorporated with biopolymers (starch and pectin), using a heat-drying technique (oven drying). The incorporation of biopolymers is intended to reinforce the structure of aqueous and solid foams, helping their stability and adhesion between particles. In order to confirm the good performance of the foams, the study characterized the material in terms of density, mechanical strength and general structure. To this end, the materials were prepared using aqueous dispersions of solubilized biopolymers, swollen lignocellulosic particles and the surfactant sodium dodecyl sulfate. The systems were subjected to mechanical agitation to incorporate air bubbles, producing aqueous foams with shape stability to be dried in ovens, forming solid foams. In this process, the bubbles promote the formation of pores, the anatomy of which influences the density and mechanical properties of the solid foams. The results show that the foams had a low density (0.07 to 0.26 g.cm-3) and mechanical resistance to compression compatible with the performance of plastic foams (0.08 to 0.27 MPa). The properties of these structures varied according to the type of biopolymer and biomass and the ratio between particles and biopolymers, with the foam with SB particles and starch in the particle/biopolymer ratio four being the most resistant (0.27 MPa). In addition, it was observed that particle size influences the formation of bubble scaffolds, with a tendency to reduce bubble size using smaller particles, such as from SB (0.04 to 0.05 mm). Thus, the study shows that it is possible to develop solid foams, starting from a sustainable route, with the use of unrefined plant biomass and drying in an oven. These promising results support the development of a more sustainable route to produce renewable lightweight materials, aimed at the replacement of plastic foams in packaging.
Use of unrefined plant biomass for the development of renewable foams
Keywords: Bagaço de cana-de-açúcar; Biomassa vegetal; Espumas; Resíduo industrial de eucalipto; Renovável; Eucalyptus industrial waste; Foams; Sugarcane bagasse; Renewable; Plant biomass; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES